Togo : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Togo. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that Togo's economic growth has remained strong in recent years, averaging 5.4 percent in 2013-14, on the back of productivity gains in the agricultural sector and public investment in transport infrastructure. The fast pace of public investment has laid the basis for higher growth but has also contributed to a pronounced increase in public debt and current account deficit. Output growth is expected to be sustained over the medium term, although current account and debt pressures are unlikely to abate. Growth is expected to average 5.5 percent in 2015-18, supported by agricultural production, transportation services linked to international trade, and the impact of investments in transport infrastructure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet